Cumplimiento del modelo pedagógico constructivista por los docentes; desde las planificaciones micro curriculares y en el proceso de enseñanza-aprendizaje de las asignaturas afines de las ciencias de la computación del subnivel medio de instituciones educativas de la parroquia El Sagrario del Cantón Loja durante año lectivo 2023-2024. - Abad Ruilova, Andrea Nayely (2024)
The constructivist pedagogical model resides in its ability to guide and motivate students towards the role of researcher and innovator in their own learning process. In this context, the teacher takes on the role of guide and companion in the acquisition of knowledge, using the resources available in their environment and leveraging tools of the digital era. This approach promotes the development of critical and reflective thinking, allowing for meaningful and lasting learning. The research aimed to analyze the application of the constructivist pedagogical model by teachers in the micro-curricular planning and the teaching-learning process of related computer science subjects at the middle sublevel of educational institutions in the El Sagrario parish of the Canton during the academic year 2023-2024. The methodology employed was deductive, with a quantitative exploratory-descriptive approach and a cross-sectional study. Seven teachers from the mentioned sector were selected as the sample. The results were based on the review of documents from digital repositories, indexed databases, and scientific research, leading to the construction of two research instruments. These instruments were applied through observation techniques to the teachers and their micro-curricular planning, which were integral parts of the research. The results allowed for the identification that the micro-curricular planning is based on the constructivist pedagogical model, and it was diagnosed that the teaching practices of the teachers consistently align with the aforementioned model. Keywords: Constructivist pedagogical model, micro-curricular planning, teaching-learning.